Kajian Tingkat Bahaya Erosi Dan Indeks Nilai Penting Di Hutan Rakyat Di Desa Candiwulan Kecamatan Kutasari Kabupaten Purbalingga - Gunanto Eko Saputro; Moh. Husein Sastranegara (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
This study was aimed at assessing the danger level of erosion, vegetation conditions, and the relationship between the level of erosion and vegetation in the community forest in Candiwulan Village, District Kutasari, Purbalingga. The results showed that the rate of erosion in forest areas studied was at 56.62 or go to class II or mild (erosion rate between 15-60 tonnes / ha / year), plants that are found in forest areas quite diverse.  There are12 plant seedling species, 14 species of saplings plants, 11 species of pole plants and 12 species of trees.  While in zone II there were only 9 plant species.  The calculation included the relative density, relative frequency and relative dominance to known important value index (IVI) to determine the role of each of the plants in both zones. The dominant role of plants at the seedling stage is coffee with IVI 70.49, coffee saplings showed INP 51.77,  the teak poles with IVI 76.69 and tree of Albizia with IVI 108.79. The vegetation diversity in the area of community forest Candiwulan Village has caused mild erosion at hazard level. The cultivating patterns and the type of crops cultivated influence the erosion and run off because it affects the land and the soil cover and the production of organic material that serves as a ground cover.